Pembelajaran berbasis pengabdian (service learning) pada program magang di Perpustakaan Pusat Survei Geologi - Muhammad Rifky Fauzan; Nizam Mikhalfani; Sri Yuniarti (Universitas Pendidikan Indonesia, 2026)
The Library and Information Science Study Program at the Universitas Pendidikan Indonesia (UPI) is one of the programs that produce prospective librarians in Indonesia. Librarians are required to keep up with the times, so the Library and Information Science Study Program of UPI is obliged to provide opportunities for prospective librarian students to improve their competencies through internships. The purpose of this community service is to determine the implementation of service learning in the Program Penguatan Profesional Kepustakaan Non-Kependidikan (P3KNK) carried out by UPI students at the Geological Survey Central Library. The methods used include pre-implementation, implementation, and post-implementation stages. The results obtained during the program implementation: students carried out various activities, starting from inventorying collections in the form of data entry from library shelves to Google Sheets, checking shelf locations in SLiMS, checking collection locations on the GeoKids service, and converting rare collections in physical form into digital format using a scanner with the results in PDF files. Overall, this P3KNK activity provided deeper insights into library management applicable to institutional libraries, especially special libraries, and offered solutions that can be implemented to improve the quality of library services in the future.